Characteristics and Strategies of Rooftop Farming in Jakarta for Sustainable Development - Fasya Miftah Akbar; Eva Sanchia Janita; Mushlih Muharrik; Ahmad Giffari; Andhika Ajie; Arimbi Putik Apsari (Pusbindiklatren Bappenas, 2025)
This study explores the characteristics and implementation strategies of rooftop farming in Jakarta as a response to urban food insecurity and sustainability challenges. Using a mixed-methods approach, comprising literature review, semi-structured interviews, and policy gap analysis, the study investigates rooftop farming practices across 27 sites in Jakarta. It examines infrastructure, market access, and institutional support. The findings reveal limited access to funding, technology, and formal guidance, despite the practice’s potential to enhance food security and green infrastructure. Comparative insights from cities such as Singapore and Melbourne highlight the effectiveness of targeted incentives and integrated planning. The study proposes practical policy recommendations, including technical guidelines, subsidies, urban spatial integration, and public education programs. These measures aim to support a more resilient and sustainable urban food system in Jakarta.